The influence of stray inductance of tested object on technical performance of electrical capacitance meters with phase detectors - Kostiukov, Ivan Aleksandrovich (Національний технічний університет "Харківський політехнічний інститут", 2019)
Control of technical state of electrical insulation by means of applying of electrical capacitance and power loss factor as informative parameters is complicated by the presence of stray parameters of tested capacitive object. The influence of stray inductance of tested objecton technical performance of measurement scheme based on applying of phase detector and voltage to current converter is considered in this paper. It was shown that the presence of inevitable stray inductance of tested object causes changes of active and reactive components of voltage on the output of phase sensitive detector. According to the results of carried out analysis, stray inductance canalso lead to the existence of substantial frequency dependence of electrical capacitance of tested object even in case of applying non-polar dielectric materials and to the distorted values of power loss factor of tested dielectric material. Finally, it was shown that the presence of stray inductance causes difficulties in estimation of technical state of electrical insulation due to substantial discrepancy between the value of effective capacitance, which has been measured under the influence of stray inductance, and the exact value of capacitance which implies negligible stray inductance. Considered in this paper deleterious influence of stray inductance and resonant phenomena on accuracy of carried out appraisal of technical state of tested capacitive object should betaken into consideration in case of applying measurement schemes with phase detectors.

Проведено аналіз впливу паразитної індуктивності ємнісного об’єкту контролю та схеми вимірювання на результати контролю електричної ємності та тангенса кута діелектричних втрат при використанні вимірювальних схем, побудованих на використанні фазових детекторів та перетворювачів напруги в струм. Показано, що наявність паразитної індуктивності об’єкту контролю призводить до збільшення значень електричної ємності та тангенса кута діелектричних втрат і, крім того, до збільшення активної та реактивної компонент напруги на виході фазового детектора.
Вплив паразитної індуктивності об’єкту контролю на роботу вимірювачів електричної ємності із фазовими детекторами
Keywords: dielectric losses; humidity control; electrical insulation; діелектричні втрати; контроль зволоження; електрична ізоляція